The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12885-016-3031-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of SCN9A are associated with oxaliplatin-induced neuropathy

Abstract: BackgroundOxaliplatin is a chemotherapy agent active against digestive tumors. Peripheral neuropathy is one of the most important dose-limiting toxicity of this drug. It occurs in around 60–80% of the patients, and 15% of them develop severe neuropathy. The pathophysiology of oxaliplatin neurotoxicity remains unclear. SCN9A is a gene codifying for a subtype sodium channel (type IX, subunit α) and mutations in this gene are involved in neuropathic perception. In this study we investigated whether SCN9A genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
(29 reference statements)
1
15
1
Order By: Relevance
“… 24 Recent pharmacogenetic studies have investigated target genes in the oxaliplatin metabolism, detoxification, or excretion pathways to predict severe OIPN. 27 28 29 The present study identified reductions of the a-SAP of >11.5% in the median nerve between baseline and four cycles ( p =0.031) and of >22.5% in the sural nerve between four and eight cycles ( p =0.031) as early predictors of the development of severe OIPN at the end of treatment. These findings are similar to a >30% decrease in the a-SAP from the baseline value in the radial and dorsal sural nerves mid-treatment being associated with severe OIPN at the end of treatment.…”
Section: Discussionsupporting
confidence: 51%
“… 24 Recent pharmacogenetic studies have investigated target genes in the oxaliplatin metabolism, detoxification, or excretion pathways to predict severe OIPN. 27 28 29 The present study identified reductions of the a-SAP of >11.5% in the median nerve between baseline and four cycles ( p =0.031) and of >22.5% in the sural nerve between four and eight cycles ( p =0.031) as early predictors of the development of severe OIPN at the end of treatment. These findings are similar to a >30% decrease in the a-SAP from the baseline value in the radial and dorsal sural nerves mid-treatment being associated with severe OIPN at the end of treatment.…”
Section: Discussionsupporting
confidence: 51%
“…A recent study suggested that SNPs in voltage-gated sodium channel genes (SCN9A-rs6754031 and SCN10A-rs12632942) can cause oxaliplatin-based peripheral neurotoxicity [24,25,33,34]. A polymorphism in SCN9A (rs6746030) was also reported to be associated with decreased neurotoxicity [35]. However, these polymorphisms were not associated with TIPN in our study.…”
Section: Discussioncontrasting
confidence: 67%
“…The development of acute oxaliplatin-induced peripheral neuropathy was altered in patients with single-nucleotide polymorphisms in SCNA genes encoding selected Na v channels. A polymorphism (rs2302237) in the SCN4A gene, which encodes the Na v 1.4 channel and a polymorphism (rs1263292) in the SCN10A coding for Na v 1.8 channel have been associated with an increased incidence of acute oxaliplatin-induced CIPN [27], while a polymorphism (rs6746030) in the SCN9A gene, which encodes the Na v 1.7 channel, protected against severe oxaliplatin-induced CIPN [28].…”
Section: Genetic Polymorphisms Associated With Oxaliplatin-induced Nementioning
confidence: 99%